The influence of learning and growth and prosocial behavior on the accountability of village financial management moderate by a participative leadership style - Asti M, Choirunnisa; Lismawati, Lismawati (Institute of Computer Science (IOCS), 2024)
This research employs a quantitative approach to investigate the interplay between learning and growth, prosocial behavior, and the accountability of village financial management, with a focus on the moderating role of participative leadership. Utilizing Structural Equation Modeling (SEM) with Partial Least Square (PLS) components through WarpPLS 7.0 software, the findings reveal that both learning and growth (X1) and prosocial behavior (X2) positively impact village financial management accountability (Y). However, the participative leadership style (X3) does not significantly strengthen these influences, as indicated by its negligible path coefficients and p-values. In summary, the study underscores the substantial and affirmative contributions of learning, growth, and prosocial behavior to the accountability of village financial management, while highlighting the limited moderating impact of a participative leadership style in this context